Antegrade or Retrograde Approach for the Management of Tandem Occlusions in Acute Ischemic Stroke: A Systematic Review and Meta-Analysis - Min, Xiaoli; Du, Jianhua; Bai, Xuesong; Wei, Tao; Dmytriw, Adam A.; Patel, Aman B.; Zhang, Xiao; Xu, Xin; Feng, Yao; Wang, Tao; Wang, Xue; Yang, Kun; et al. (Frontiers in Neurology, 2022)
Background: Acute ischemic stroke (AIS) caused by tandem intracranial and extracranial occlusions is not rare. However, optimal strategy between antegrade (extracranial first) or retrograde (intracranial first) approaches still remains elusive. This systematic review and meta-analysis aim to compare the two approaches to provide updated clinical evidence of strategy selection. Methods: PubMed, Ovid, Web of Science, and the Cochrane Library were searched for literature comparing antegrade and retrograde approaches for patients with AIS with concomitant tandem occlusions. Outcomes including successful reperfusion [Throbolysis in Cerebral Infarction (TICI) 2b−3] and 90-day favorable outcome [modified Rankin Scale (mRS) 0–2], any intracerebral hemorrhage, symptomatic intracerebral hemorrhage, procedural complications, and mortality were evaluated. The risk of bias was assessed using the Newcastle–Ottawa Scale and illustrated in the Funnel plot. Heterogeneity was assessed by I2 statistic. Subgroup and sensitivity analyses were also performed. Results: A total of 11 studies accounting 1,517 patients were included. 831 (55%) patients were treated with an antegrade approach and 686 (45%) patients were treated with the retrograde approach. A higher successful reperfusion rate was achieved in retrograde group than that of antegrade group [83.8 vs. 78.0%; odds ratio (OR): 0.63, 95% CI: 0.40–0.99, p = 0.04]. 90-day favorable outcome (mRS 0–2 at 90 days) also showed significantly higher in retrograde group compared with antegrade group (47.3 vs. 40.2%; OR: 0.72, 95% CI: 0.58–0.89, p = 0.002). The incidence of any intracranial hemorrhage (ICH), symptomatic intracranial hemorrhage, 90-day mortality, and other complications did not differ between two groups. Conclusion: In AIS with tandem occlusions, the retrograde approach might achieve a higher successful reperfusion rate and better functional outcome with a comparable safety profile when compared with an antegrade approach. Further prospective controlled studies with more meticulous design and a higher level of evidence are needed to confirm these results. Systematic Review Registration: “PROSPERO” database (CRD 42020199093), https://www.crd.york.ac.uk/PROSPERO/.